PENGARUH KOMPETENSI, PENGENDALIAN INTERN AKUNTANSI, TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN (Studi pada Satker Vertikal Kementerian Kesehatan Wil Prov. DKI Jakarta) - Muhamad Nur Ihwan; Tri Widyastuti; Widarto Rachbini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This research is to examine obtain empirical evidence related the factors that influence government financial statement quality. Based on PP No. 71 year 2010, government financial statement quality have to meet the qualitative characteristic, where are factors that influence are competency, accounting intern control and information technology. The study was conducted on the staf who responsbility doing the accounting in the office that unit of ministry of healthy in Jakarta City, using primary data obtained from questionnaires distributed to respondents. Sampling through purposive sampling and obtained of 51 respondents. The collected data was processed using SPSS version 21 and the statistic method used to analize was multiple linier regression.the data analysis results showed all of research instruments are valid, reliable and feasible model used to explain the dependent variable. The results showed that the competency,accounting intern control and information technology have signifikan positive impact on quality of financial statement. Keywords: Government financial statement, competency, accounting intern control, and information technology.